The effect of atherosclerosis progression and exacerbation by diabetes on fibrinolysis - Di Giuseppantonio, Luca (My University, 2019)
Atherosclerosis is a chronic inflammatory disease characterized by plaque or clot build-up in the arterial vessel wall, which leads to blood vessel occlusion and consequently heart attack and stroke. Diabetes is a metabolic disorder characterized by elevated sugar (hyperglycemia), which is a known risk factor for the development and exacerbation of atherosclerosis. Recent studies identified fibrinolytic factors (e.g. plasminogen activator inhibitor 1 (PAI-1), thrombin-activatable fibrinolysis inhibitor (TAFI)) that are linked with worsening of atherosclerosis and diabetes. In addition, since activated TAFI (TAFIa), possesses both antifibrinolytic and anti-inflammatory properties, it is a molecule of interest within the context of atherosclerosis progression. Therefore, we hypothesize that fibrinolysis is influenced by atherosclerosis and diabetes. To test this, we used mice that are prone to developing atherosclerosis (ApoE-/-) and hyperglycemia (Ins2+/Akita) from which the heart and plasma samples were collected at 15- or 25-weeks of age. Overall, no differences in plasma clot lysis times were observed between male (hyperglycemic) and female (normal glycemic) ApoE-/-:Ins2+/Akita mice. Quantitation of plaque volume showed a significant increase at 25-weeks compared with 15-weeks, consistent with previous reports. Closer examination revealed that in 15-week-old mice, plaque volume and PAI-1 levels displayed a trend with lysis time, but not in 25-week-old mice. The lysis times showed no difference with hyperglycemia or age. When TAFIa was inhibited, 15-week-old mice had longer lysis times compared with 25-week-old mice independent of hyperglycemia. In addition, elevation of cholesterol and triglyceride levels from hyperglycemia were only observed at 15-weeks. Total PAI-1 levels appeared to decrease with age. TAFI zymogen levels did not change with hyperglycemia or age. Fragment 1.2 levels, which indicate coagulation activation/thrombin generation increase with age but were not correlated with hyperglycemia. Overall, hyperglycemia does not appear to impact fibrinolysis directly, but rather indirectly through atherosclerosis in ApoE-/-:Ins2+/Akita mice.
Keywords: atherosclerosis; diabetes; fibrinolysis